Validity and Reliability of Self-Concept Instrument Using Rasch Model - Latifah, Meyliani; Saripah, Ipah; Suryana, Dodi; Sunarya, Yaya (Jurnal Kajian Bimbingan dan Konseling, 2024)
The development of instruments designed to assess student self-concept is crucial. This understanding of self-concept is based on the premise that it is a dynamic and ever-evolving construct. The concept of self-concept is initially conceived as a unidimensional structure but subsequently evolves into a multidimensional construct. The present study assesses the validity and reliability of the newly developed self-concept instrument. In Indonesia, there is a paucity of research that employs the Rasch Model to examine self-concept instruments, particularly in the context of the junior high school population. The objective of this study was to analyze the self-concept instrument using the Rasch Model with a sample of 113 students at the junior high school level. The research methodology employed is quantitative, with a cross-sectional design. The sampling technique employed was simple random sampling. The findings of the study indicate that the instrument effectively assesses the intended dimensions of self-concept. The reliability of the self-concept instrument is deemed to be of a high category, while the reliability of the self-concept item is considered to be of an excellent standard.